CMIP6 climate scenarios for climate adaptation studies in Zambia - Sahana, V.; Panjwani, Shweta; Amarnath, Giriraj (2024)
This study investigates provincial-level extreme weather conditions over Zambia using the Coupled Model Intercomparison Project (CMIP6) climate projections for various emission scenarios from 25 Global Climate Models (GCMs). Taylor diagram analysis is performed to identify the best-performing GCMs by evaluating precipitation and temperature variables with the observed datasets for the baseline period (1950-2014). Earlier studies have investigated the changes in precipitation and temperature variables alone. This study investigates the trends in Annual Precipitation, Annual temperature (mean, maximum and minimum) as well as Standardized Precipitaion Evapotranspiration Index (SPEI) for the near future (2021-2060) and far future (2061-2100) using Sen’s Slope Estimator. While all the projected climate scenarios depict an increasing trend in the mean temperatures for both near and far future periods, upto 4˚C increase is expected at the end the 21st century under the worst-case scenario-SSP5-8.5. An overall decrease (upto -65 mm) in precipitation is expected in the near future and far future periods across the country, expect the North-eastern provinces. Corroborating with such a spike in climate conditions, the SPEI decreases by -1.16, -0.95, -0.86, -0.83 (near future, 2021-2060) and -1.36, -1.75, -1.98 and -1.99 (far future, 2061-2100) for SSP1-2.6, SSP2-4.5, SSP3-7.0, SSP5-8.5 respectively. Larger changes in SPEI is observed in Western, Southern, Northwestern and Lusaka provinces in both near and far future indicating worst drought conditions. The outcome from the present study provides a basis for undertaking provincial-level adaptation and mitigation measures under the evolving climate and framing policy interventions to combat climate change.